Smart technologies in ornamental horticulture - Prasad, K V; Kumar, S P Jeevan; K, Prabha (Indian Horticulture, 2024)
Digital technology has played a prominent role in precision agriculture particularly Internet-of-things (IoT) and Artificial intelligence (AI). These technologies use drones, sensors and GPS mapping to optimize the crop inputs with concomitant increase in yields and significant reduction in waste. Monitoring of plant growth and health would enable growers to supplement precise fertilization and irrigation as well as pest management practices which will ultimately reduce the environmental impact on flower production.